Tricyclic antidepressant treatment evokes regional changes in neurotrophic factors over time within the intact and degenerating nigrostriatal system - Paumier, Katrina L. (Exp Neurol, 2015)
In addition to alleviating depression, trophic responses produced by antidepressants may regulate neural plasticity in the diseased brain, providing not only symptomatic benefit but potentially slowing the rate of disease progression in Parkinson’s disease (PD). Recent in vitro and in vivo data provide evidence that neurotrophic factors such as brain derived-neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF) may be key mediators of the therapeutic response to antidepressants. As such, we conducted a cross-sectional time-course study to determine whether antidepressant-mediated changes in neurotrophic factors occur in relevant brain regions in response to amitriptyline (AMI) treatment before and after intrastriatal 6-hydroxydopamine (6OHDA). Adult male Wistar rats were divided into seven cohorts and given daily injections (i.p.) of AMI (5mg/kg) or saline throughout the duration of the study. In parallel, various cohorts of intact or parkinsonian animals were sacrificed at specific time points to determine the impact of AMI treatment on trophic factor levels in the intact and degenerating nigrostriatal system. The left and right hemispheres of the substantia nigra, striatum, frontal cortex, piriform cortex, hippocampus and anterior cingulate cortex were dissected and BDNF and GDNF levels were measured with ELISA. Results show that chronic AMI treatment elicits effects in multiple brain regions and differentially regulates levels of BDNF and GDNF depending on the region. Additionally, AMI halts the progressive degeneration of dopamine (DA) neurons elicited by an intrastriatal 6-OHDA lesion. Taken together, these results suggest that AMI treatment elicits significant trophic changes important to DA neuron survival within both the intact and degenerating nigrostriatal system.